A Longitudinal Investigation Early Speech and Language Development in Children with Cleft Palate and Lip: Examining the Impact of Cleft Palate and Lip on Early Speech and Language Development in Children (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The study was conducted using a literary meta-analysis comparing the early speech and language functioning of infants with non syndromes of the splintered lips andor the palate (NSCLP) with those without the NSCLP from birth to age 811(years months).the capacity of children with diaphragm palates to speak before to and after palate operations. All speech and language evaluations suggested that the acquisition of cleft and no cleft groups differed significantly. Children with CLP have difficulty with high-pressure consonants, especially at the alveolar location of articulation. a study that investigated the phases of language development and The Para lingual significance of the age early development of phonological and language capabilities Cleft differential types, Lipple, palate and cleft lip effect on the development of language and speech, cleft lip and palate, effect on language and languages development, cleft lips and palates Split lip influence on language and speech development, Lip and palate split, lip splitting, the phonological impact of a cleft palate The influence of delayed phonological development in split children on lexical development, Early development, longitudinal changes in mental performance, language-related factors